Implementation of Google Classroom Online Learning in Increasing Learning Interest and Motivation (A Study of BKPI Students at Wiralodra University) - Didik Himmawan; Dian Zahra Nuraeni; Hilwa Nurul Azkiya; Nilam Suci (Journal Of Psychology, Counseling And Education, 2025)
Technological advancements and developments have penetrated various areas of life, including education. In today's digital era, education has made it easier for people to learn without the constraints of distance, space, or time. The internet has made learning processes and interactions highly accessible. In fact, many students complain about this online learning system. This is because the learning provided is limited to assignments without clear explanations, and network disruptions sometimes occur during lessons. This indirectly impacts students' interest and motivation to learn. Each student has different learning interests and motivations. This research used qualitative methods with observation and questionnaire techniques. The purpose of this paper is to determine the implementation of Google Classroom online learning in increasing interest and motivation to learn among Islamic Guidance and Counseling students at Wiralodra University.